The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.ajhg.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Constraint on the Spatial Distribution of Missense Variants in Human Protein Structures

Abstract: The spatial distribution of genetic variation within proteins is shaped by evolutionary constraint and provides insight into the functional importance of protein regions and the potential pathogenicity of protein alterations. Here, we comprehensively evaluate the 3D spatial patterns of human germline and somatic variation in 6,604 experimentally derived protein structures and 33,144 computationally derived homology models covering 77% of all human proteins. Using a systematic approach, we quantify differences … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 58 publications
0
67
0
Order By: Relevance
“…Our data also suggests the possible existence of an as-yet unidentified interaction of Menin, as evidenced by the cluster of pathogenic variants lying on the protein surface opposite the JunD binding pocket. Notably, MEN1 has recently been identified as one of the genes exhibiting significant spatial clustering of pathogenic variants (47); our analysis suggests that this clustering is likely to apply both to regions of structural importance, which are buried in the interior of the protein, and to surface regions which form essential interactions with binding partners.…”
Section: Discussionmentioning
confidence: 73%
“…Our data also suggests the possible existence of an as-yet unidentified interaction of Menin, as evidenced by the cluster of pathogenic variants lying on the protein surface opposite the JunD binding pocket. Notably, MEN1 has recently been identified as one of the genes exhibiting significant spatial clustering of pathogenic variants (47); our analysis suggests that this clustering is likely to apply both to regions of structural importance, which are buried in the interior of the protein, and to surface regions which form essential interactions with binding partners.…”
Section: Discussionmentioning
confidence: 73%
“…This improvement in classification ability for LOF variants in SCN5A when adding functional density for peak current (0.69 without vs. 0.78 with, p = .01) suggests structure-based features contribute information not contained in other predictive features (Fig. S8) an observation gaining appreciation elsewhere [ [42] , [43] ].…”
Section: Resultsmentioning
confidence: 97%
“…Our previous work 34,35 has shown that evaluating the Euclidean distance in 3D space of uncharacterized variants relative to pathogenic and benign variants can aid in variant prioritization. Sivley et al 34,35 developed a program called PathProx that evaluates the relative 3D proximity of a variant to known pathogenic and benign variants.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work 34,35 has shown that evaluating the Euclidean distance in 3D space of uncharacterized variants relative to pathogenic and benign variants can aid in variant prioritization. Sivley et al 34,35 developed a program called PathProx that evaluates the relative 3D proximity of a variant to known pathogenic and benign variants. To explore the spatial distribution of variants in AP‐4, we mapped onto the AP‐4 homology model four reported pathogenic variants (curated from the literature) 13–16,36 and six variants annotated as likely pathogenic in ClinVar (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation